2016
DOI: 10.1115/1.4034515
|View full text |Cite
|
Sign up to set email alerts
|

Development and Test of Oxide/Oxide Ceramic Matrix Composites Combustor Liner Demonstrators for Aero-engines

Abstract: Ceramic matrix composites (CMC) offer the potential of increased service temperatures and are thus an interesting alternative to conventional combustor alloys. Tubular combustor liner demonstrators made of an oxide/oxide CMC were developed for a lean combustor in a future aero-engine in the medium thrust range and tested at engine conditions. During the design, various aspects like protective coating, thermomechanical design, and development of a failure model for the CMC as well as design and test of an attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Improving environmental performances and efficiency of aircraft engines is essential for answering the increase of global aircraft traffic of 4.4% per year predicted by the industry 1 . In this regard, new gas turbine technologies like combustor components based on high temperature ceramic matrix composites (CMCs) are developed since the 1990s 2–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving environmental performances and efficiency of aircraft engines is essential for answering the increase of global aircraft traffic of 4.4% per year predicted by the industry 1 . In this regard, new gas turbine technologies like combustor components based on high temperature ceramic matrix composites (CMCs) are developed since the 1990s 2–5 …”
Section: Introductionmentioning
confidence: 99%
“…1 In this regard, new gas turbine technologies like combustor components based on high temperature ceramic matrix composites (CMCs) are developed since the 1990s. [2][3][4][5] In almost all aero gas turbines combustion occurs in a rich lean staged combustor. At the upstream end of the combustor an air fuel mixture with a fuel-rich equivalence ratio is injected and combustion is stabilized by recirculated hot combustion products.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous fiber reinforced ceramic matrix composites (CMC) are being used in many fields, such as aeronautical, aerospace and automobile, because of their excellent thermomechanical properties at high temperatures and relatively low density when compared to their metallic counterparts [1][2][3][4][5]. Filament winding technology is one of the preforming methods which is employed to manufacture CMCs with rotational symmetry axis and application-tailored fiber orientation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of Y 2 O 3 as EBC for oxide‐based WHIPOX CMCs has been studied by Mechnich et al and was also demonstrated on real combustor components . Prior to coating by atmospheric plasma spraying (APS), a reaction‐bonded aluminium oxide (RBAO) bond coat was applied to increase the adhesion of the coatings to the substrate and reduce the gas permeability of the sample .…”
Section: Introductionmentioning
confidence: 99%